‘No Longer Languished in the Periphery of Existence:’ female bodies, emotions, and Malay folktales - Wan Nur Madiha Ramlan; Mohd Muzhafar Idrus; Nurul Izzati Hassan (Penerbit Universiti Kebangsaan Malaysia, 2025)
The marginalisation of women in folktales generally exists within the undermined, peripheral female characters. This article takes up this very challenge to revisit and rearticulate such a marginalisation by exploring the representations of the female body through an analysis of recurring emotional patterns. These characters include Mahsuri, Puteri Lindungan Bulan, Puteri Gunung Ledang, Deruma of Si Tanggang, Tanjung of Batu Belah Batu Bertangkup, and Mak Labu of Bawang Merah Bawang Putih. Specifically, this article presents a computational approach to understanding how female characters and subjectivities are portrayed across these narratives. By employing sentiment analysis functions and Robert Plutchik’s Wheels of Emotions, comprising eight fundamental extended degrees of emotions, Malay folktale texts in the English language are processed for word frequency, emotional polarity, and intensity to unveil the palimpsestic depth of women's depictions involving the human body and sociocultural representations concerning body imagery. By exposing these layered emotional arcs and the ways female characters shift between prized virtues and punitive portrayals, the study reframes inherited narratives and demonstrates sentiment and emotion analysis as powerful tools for uncovering subtle biases and evolving agency in literary traditions.